Exploring the impact of CMIP5 model biases on the simulation of North Atlantic decadal variability. Issue 14 (16th July 2015) - Menary, Matthew B.; Hodson, Daniel L. R.; Robson, Jon I.; Sutton, Rowan T.; Wood, Richard A.; Hunt, Jonathan A.
Abstract Instrumental observations, paleoproxies, and climate models suggest significant decadal variability within the North Atlantic subpolar gyre (NASPG). However, a poorly sampled observational record and a diversity of model behaviors mean that the precise nature and mechanisms of this variability are unclear. Here we analyze an exceptionally large multimodel ensemble of 42 present‐generation climate models to test whether NASPG mean state biases systematically affect the representation of decadal variability. Temperature and salinity biases in the Labrador Sea covary and influence whether density variability is controlled by temperature or salinity variations. Ocean horizontal resolution is a good predictor of the biases and the location of the dominant dynamical feedbacks within the NASPG. However, we find no link to the spectral characteristics of the variability. Our results suggest that the mean state and mechanisms of variability within the NASPG are not independent. This represents an important caveat for decadal predictions using anomaly assimilation methods.